Metabolite profiling and identification of novel umami compounds in the chaya leaves of two species using multiplatform metabolomics. (15th March 2023) - Hutasingh, Nuti; Chuntakaruk, Hathaichanok; Tubtimrattana, Apinya; Ketngamkum, Yanisa; Pewlong, Putthamas; Phaonakrop, Narumon; Roytrakul, Sittiruk; Rungrotmongkol, Thanyada; Paemanee, Atchara; Tansrisawad, Nat; Siripatrawan, Ubonrat; Sirikantaramas, Supaart
Highlights: Metabolite variation in two species of chaya leaves was described. Young chaya leaves exhibited high umami taste intensity. l -glutamic acid and 5′-adenosine monophosphate accumulated in young leaves. Quinic acid, trigonelline, and other small peptides are novel umami compounds. Abstract: Chaya ( Cnidoscolus chayamansa and C. aconitifolius ) is a fast-growing medicinal plant, and its leaves exhibit a strong umami taste. Here metabolite variation and umami-related compounds in the leaves of two chaya species were determined using a multiplatform untargeted-metabolomics approach, electronic tongue, and in silico screening. Metabolite profiles varied between the leaves of the two species and among leaf maturation stages. Young leaves exhibited the highest umami taste intensity, followed by mature and old leaves. Partial least square regression and computational molecular docking analyses revealed five potent umami substances (quinic acid, trigonelline, alanyl–tyrosine, leucyl–glycyl–proline, and leucyl–aspartyl–glutamine) and three known umami compounds (l -glutamic acid, pyroglutamic acid, and 5′-adenosine monophosphate). The five substances were validated as novel umami compounds using electronic tongue assay; leucyl–glycyl–proline exhibited synergism with monosodium glutamate, thereby enhancing the umami taste. Thus, substances contributing to the taste of chaya leaves were successfully identified.